PIK3R1 mutations in SHORT syndrome - Schroeder, Christopher Maximilian; Riess, A.; Bonin, M.; Bauer, P.; Riess, O.; Döbler‐Neumann, M.; Wieser, S.; Moog, Ute; Tzschach, A. (Clinical genetics, 2014)
SHORT syndrome (OMIM 269880) is a rare autosomal-dominant disorder characterized by short stature, hyperextensibility of joints, hernias, ocular depression, ophthalmic anomalies (Rieger anomaly, posterior embryotoxon, glaucoma), teething delay, partial lipodystrophy, insulin resistance and facial dysmorphic signs. Heterozygous mutations in PIK3R1 were recently identified in 14 families with SHORT syndrome. Eight of these families had a recurrent missense mutation (c.1945C>T; p.Arg649Trp). We report on two unrelated patients with typical clinical features of SHORT syndrome and additional problems such as pulmonary stenosis and ectopic kidney. Analysis of PIK3R1 revealed the mutation c.1945C>T; p.Arg649Trp de novo in both patients. These two patients not only provide additional evidence that PIK3R1 mutations cause SHORT syndrome, but also broaden the clinical spectrum of this syndrome and further confirm that the amino acid exchange c.1945C>T; p.Arg649Trp is a hotspot mutation in this gene.